ANALISIS PENGGUNAAN SISTEM INFORMASI AKUNTANSI ACCURATE ONLINE DALAM PENGELOLAAN PERSEDIAAN BARANG DAGANG STUDI KASUS PT XYZ - Adira Nur Asyifa; Lediana Sufina (Ibs Press, 2025)
This study aims to analyze the use of the Accurate Online Accounting Information System (AIS) in managing merchandise inventory at PT XYZ. The research objectives include identifying the systems and procedures of the inventory AIS, examining how the company utilizes the Accurate Online features for recording and managing stock, and identifying factors that hinder its effectiveness, such as technical limitations, user understanding, and technological infrastructure. This research employs a qualitative method with data collected through observation, interviews, and literature study. The results indicate that the implementation of the purchasing cycle at PT XYZ is not yet fully aligned with James A. Hall’s theory, as the process remains manual without formal documentation and layered authorization. Furthermore, Accurate Online has not been optimally utilized for control and automatic recording. In terms of internal control, the system’s implementation is not fully consistent with the COSO framework, as indicated by the lack of written policies, risk assessments, and formal authorization procedures.